Horses seropositive for Toxoplasma gondii, Sarcocystis spp. and Neospora spp.: Possible risk factors for infection in Brazil. (October 2016) - Cazarotto, Chrystian J.; Balzan, Alexandre; Grosskopf, Rhayana K.; Boito, Jhonatan P.; Portella, Luiza P.; Vogel, Fernanda F.; Fávero, Juscivete F.; de C. Cucco, Diego; Biazus, Angelisa H.; Machado, Gustavo; Da Silva, Aleksandro S.
Abstract: Many parasitic diseases are considered asymptomatic, even though some studies have shown that they may cause pathological changes in the host. Therefore, the aim of this study was to evaluate the occurrence of antibodies against Toxoplasma gondii, Neospora spp. and Sarcocystis spp. in horses, and to identify the risk factors for disease. For this, 174 horses were studied, 90 males and 84 females aged between two and 20 years old. Blood samples were collected and stored in tubes without anticoagulant to obtain serum, which was subjected to serological tests for T. gondii, Sarcocystis spp., and Neospora spp. using indirect immunofluorescence assay (IFA). IFA results were as follows: Sarcocystis spp. 41.37% (72/174) (CI95%-34.05–49.09); T. gondii 32.18% (56/174) (CI95%-25.42–39.74) and Neospora spp. 48.27% (84/174) (CI95%-40.68.50–55.93). Out of 174 horses, 81 had simple infection, 61 had mixed infections with two or three of these pathogens, and therefore, only 32 horses showed no antibodies to any of these pathogens. No risk factors for Sarcocystis spp. and T. gondii infection were identified. However, there was a significant (1.22-CI95%-1.02–1.52) relationship between animal age and Neospora spp. infection, since older animals showed higher prevalence. Therefore, it was possible to conclude that T. gondii and Neospora spp. affect horses in Southern Brazil, however all the animals studied were asymptomatic without reproductive, neurological or locomotor problems. Highlights: Many parasitic diseases are asymptomatic, but cause pathological changes in the host. Neospora spp., Sarcocystis spp. and Toxoplasma gondii are obligate intracellular parasites. T. gondii, Neospora spp. and Sarcoscystis spp. affect horses in Southern Brazil with a high occurrence of seropositives. Age was identified as a risk factor for Neospora spp. infection, being older animals more susceptible.